Ardisia krauensis, a new species of Primulaceae (Myrsinoideae) from Peninsular Malaysia - Avelinah Julius; Suhaimi Syahida-Emiza; Timothy M. A. Utteridge (Pensoft Publishers, 2023)
Ardisia krauensis, a new species of Primulaceae from Peninsular Malaysia, is described and illustrated. The new species is assignable into subgenus (§) Pyrgus on account of specialised lateral reproductive branches bearing a terminal inflorescence subtended by foliose bracts. Morphologically, the new species mostly resembles Ardisia rigida in having elliptic leaves. However, the new species can be distinguished by the combination of its lateral veins number, the inflorescence branching pattern, the rachis and flower colour, and the stigma shape. Ardisia krauensis is found in an entirely protected habitat, thus, it is assessed as Least Concern (LC).